Conventional and microwave combustion synthesis of optomagnetic CuFe2O4 nanoparticles for hyperthermia studies. (April 2018) - Kombaiah, K.; Vijaya, J. Judith; Kennedy, L. John; Bououdina, M.; Al-Najar, Basma
Abstract: Nanosized copper ferrite (CuFe2 O4 ) nanoparticles have been prepared by conventional (CCM) and microwave (MCM) combustion methods using Hibiscus rosa sinensis plant extract as a fuel. XRD and rietveld analysis confirmed the formation of single cubic phase and with crystallite size varying from 25 to 62 nm owing to grain growth after calcination. FT-IR analysis confirms the modes of the cubic CuFe2 O4 phase, due to the stretching and bending vibrations. Spherical shaped particles are observed by scanning electron microscopy and the average particle size is found to be in the range of 50–200 nm. The chemical composition is confirmed by energy dispersive X-ray analysis. The optical band gap energy estimated using Kubelka-Munk function with the help of UV–Visible diffused reflectance spectroscopy, is found to be 2.34 and 2.22 eV for CCM and MCM respectively. Photoluminescence analysis indicates that both samples absorb light in the UV–visible region and exhibit emissions at 360, 376, and 412 nm. Magnetic measurements indicate a ferromagnetic behavior, where both magnetic properties very much influenced by the preparation method and calcination temperature: both saturation magnetization and coercivity are found higher when using CCM and MCM; from 29.40 to 34.09 emu/g while almost double from 224.4 to 432.2 Oe. The observed changes in physical properties are mainly associated with crystallinity, particle size, better chemical homogeneity, and cations distribution among tetrahedral/octahedral sites. The maximum specific absorption rate obtained was 14.63 W/g, which can be considered suitable and favorable for magnetic hyperthermia. This study highlighted the benefits of green synthesis of CuFe2 O4 nanoparticles providing better magnetic properties for the platform of hyperthermia application. Highlights: Microwave combustion method is a simple and efficient route for the synthesis of nanoparticles. Plant extract plays a role of a fuel with a coordinating action. High purity single-phase cubic CuFe2 O4 structure was reported. CuFe2 O4 prepared by MCM showed better self heating efficiency.